Development of a new microscopic passing maneuver model for two-lane rural roads. (March 2015) - Llorca, Carlos; Moreno, Ana Tsui; Lenorzer, Annique; Casas, Jordi; Garcia, Alfredo
Highlights: Specific characteristics of two-lane roads require special microsimulation models. The interaction with oncoming vehicles makes passing a complex task. This study developed a new passing model for Aimsun software, including 3 steps: desire, decision and execution. More than 1750 video-recorded passing maneuvers to calibrate the new model. The new model incorporated the effect of sight distance, delay and multiple passing maneuvers. Abstract: Microsimulation is a useful tool to analyze traffic operation. On two-lane highways, the complexity of passing and the interaction with oncoming traffic requires specific models. This study focused on the development of a passing desire, decision and execution model. Results of the observation of 1752 maneuvers on 10 rural roads in Spain were used for this development. The model incorporated the effect of new factors such as available sight distance, delay and remaining travel time until the end of the highway segment. Outputs of the model were compared to observed data: firstly, individual passing maneuvers; secondly, traffic flow, percent followers and number of passing maneuvers in four single passing zones with two different traffic levels. The model was validated in four alternative passing zones.